Connectivity of medium airports in Thailand - Charukit Chaiwan (2018)
© IEOM Society International. Airports are expanding their facilities in respond to increasing number of passengers. Airport connectivity is one of indicators to evaluate airport performance. Airport connectivity can be define as the airline network of airport, related to frequency of flight and number of flights from origin to destination. Airport with good connectivity is attractive for passengers. This paper aimed to evaluate airport connectivity of medium sized airports in Thailand, which are Sakon Nakhon airport (SNO), Nakhon Phanom airport (KOP), Nannakhon airport (NNT), Phitsanulok airport (PHS) and Trang airport (TST) by using NETSCAN model during October, 2017. It was found that Phitsanulok airport (PHS) has the highest connectivity unit, with more frequency of flights.